Transimperial Eyes: An Interdisciplinary Analysis of Colonial Narratives about the Dutch Expedition to Southern Chile (1643) - Aurora Sambolín Santiago; Hugo Romero-Toledo; Matthias Gloël (Heritage, 2023)
The review of historical archives that allow us to know the observations and experiences of those who recorded scarcely explored territories in the past, especially in the context of European colonization of vast areas of the world in the seventeenth century is crucial for heritage studies. The following article analyzes how the Dutch expedition to southern Chile during the 17th century (1642–1643) was narrated, both in Dutch and in its translations into German, English, and Spanish, considering the interests of empires and the discursive differences that translational variations reveal. This transdisciplinary analysis, combining historiography, translation studies, and historical geography, consists of a critical reading of the original narration and a comparative reading of the aforementioned translations, and within them ethnographic representations made about the Mapuche-Huilliche people and the city of Valdivia and changes introduced by different translations are identified. These changes are then related to imperial contexts and discourses that shape these translations. In terms of our findings, we note that, in general, Chilean translations tend to exaggerate the representations of indigenous people as barbaric, inferior, and uncivilized. These representations are present in the European versions, but the shifts that we identified indicate an intensification of this discourse.